Importance of Work’s Perception in the Teaching Process - Aukštkalnytė, Dėja; Gerulis, Saulius (Acta Paedagogica Vilnensia, 2003)
In the present society of information a sagacity of different scientific trends is closely interacting and interweaving. Great possibilities show up for comparison the ideas and statements prevailing in various sciences in different periods. The paper makes an attempt to elucidate some theory ideas of perception of the music crystallized in phenomenology and hermeneutics. Some aspects of the defined problems are as follows. At first, the perception peculiarities. Perception is of great importance. It unavoidably supplements the essence contained in the music text. Interpretation is the act of perception. It can be expressed not only by rendition but by the verbal comment as well (when analysing what was meant and how it was expressed in a work). The paper tends to demonstrate and substantiate a divide resulting from the ideas that can be rationally illustrated in a music text (verbal comment of interpretation version) and those that can only be felt (real performance). It tries to reveal how these ideas are significant in the process of studies.